Services in the India-EU Free Trade Agreement - Hildegunn Kyvik Nordås (Örebro University School of Business, 2023)
This paper analyses the proposed free trade agreement (FTA) between EU and India focusing on services trade. Based on the text published by the European Union, I use the OECD STRI simulator to calculate the preference margin implied by the agreement and next predict the impact on services trade flows using a general equilibrium structural gravity analysis. I find that the preference margin on the STRI for Indian exports to the EU is between four and eight basis points depending on the sector, while for EU exports to India the preference margin is between 10 and 35 basis points. The predicted effect is almost a doubling of EU services exports to India, while India's services exports to the EU would increase by about 50%. EU's trade with the rest of the world would not change much, while India's exports to the rest of the world would decline by about 3%. Real services output would not change much in the EU or India. Lifting trade restrictions in the telecommunications sector is the most important policy area for facilitating services trade.
Keywords: F13; F15; F17; 330; Services; Trade; FTA; India; EU